Preparation and characterization of conductive nanostructured particles based on polyaniline and cellulose nanofibers - Casado, Ulises Martín (2014)
Conducting polyaniline (PANI) and cellulose coated PANI (PANI-NC) nanostructures with sizes of about 80–100 nm, doped with hydrochloric acid were synthesized by a sonochemical method. Both type of particles resulted electrically conductive (direct current conductivity of 0.059 and 0.075 S/cm for PANI and PANI-NC structures, respectively) and could be dispersed easily in water, leading to green colored suspensions that remain stable for more than 4 h. The morphology, crystallinity, electrical conductivity (r) and thermal stability of the obtained PANI based structures were investigated and compared. Furthermore, UV–Vis spectroscopy and rheology of water suspensions were used to explain the measured properties. Although the concentration of cellulose fibers used to synthesize the PANI-NC structures was very low, important differences respect to the neat PANI fibers regarding the microstructure, electrical conductivity and suspension behavior were found.